The Prison of Democracy Race, Leavenworth, and the Culture of Law - Benson, Sara M. (University of California Press, 2019)
Built in the 1890s at the center of the nation, Leavenworth Federal Penitentiary was designed specifically to be a replica of the US Capitol Building. But why? The Prison of Democracy explains the political significance of a prison built to mimic one of America's monuments to democracy. Locating Leavenworth in memory, history, and law, the prison geographically sits at the borders of Indian Territory (1825-1854) and Bleeding Kansas (1854-1864), both sites of contestation over slavery and freedom. Author Sara M. Benson argues that Leavenworth reshaped the design of punishment in America by gradually normalizing state-inflicted violence against citizens. Leavenworth's peculiar architecture illustrates the real roots of mass incarceration-as an explicitly race- and nation-building system that has been ingrained in the very fabric of US history rather than as part of a recent post-war racial history. The book sheds light on the truth of the painful relationship between the carceral state and democracy in the United States-a relationship that thrives to this day. "The imaginative rereading, through primary sources, of Fort Leavenworth and a host of other subjects including abolitionism, border prisons, North-South relations, and the campaign against Native Americans adds up to an original and exceptionally significant piece of research and scholarship." DESMOND KING, author of Separate and Unequal "A significant contribution to the literature regarding race, crime, and punishment. The analytical insight that the author provides through a rereading and recentering of Leavenworth is both a contribution to and an immanent critique of racialized notions of mass incarceration." DANIEL KATO, author of Liberalizing Lynching SARA M. BENSON is a Lecturer in the Department of Political Science at San Jose State University and teaches at Oakes College at the University of California, Santa Cruz.